IMPLEMENTASI PBL-STEAM TERINTEGRASI ETNOSAINS UNTUK MELATIH BERPIKIR KREATIF PADA MATERI ASAM BASA - Hazlina, Nur; Erika, Farah; Kusumaningtyas, Pintaka (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2025)
This research aims to determine the implementation of integrated PBL-STEAM ethno-science to train the creative thinking skills of eleventh-grade students at SMA Negeri 4 Samarinda on the topic of acids and bases, specifically the theory and indicators of acids and bases. This study employs a Quasi-Experimental design with a Posttest Only Control Design type. The population in this research consists of all eleventh-grade students at SMA Negeri 4 Samarinda for the academic year 2023/2024. Sampling was conducted using cluster random sampling techniques. The instrument used to measure students' creative thinking is a post-test questionnaire. Data analysis was performed using a t-test, which yielded a significance (2-tailed) of 0,017 < 0,050 for both classes, indicating that Ha is accepted, with the statement that there is an implementation of integrated PBL-STEAM ethno-science on students' creative thinking skills regarding the topic of acids and bases, specifically the theory and indicators of acids and bases. Keywords : PBL-STEAM, Ethnoscience, Creative Thinking